Effect of acid and ionic strength on the kinetics of electron transfer reaction of n-(2-hydroxy-ethyl) ethylenediamine-n, n’, n’-triacetatocobaltate (ii) complex with hypochlorite ion in aqueous acidic medium - Ahmed, Y.; D.Onu, A.; O.Idris, S.; S.Iliyasu, S.; B.Abiti, Y. (International Journal of Advanced Chemistry, 2019)
The influence of acid and ionic strength on the rate of electron transfer reaction of N-(2-hydroxy-ethyl)ethylenediamine-N,N’,N’-triacetatocobaltate(II)(hereafter, complex with Hypochlorite ion in aqueous nitric acid medium have been studied at I = 0.2 mol dm-3(NaNO3), [H+] = 1 × 10-2 mol dm-3, , T = 300 ± 1 K and λmax = 525 nm. Stoichiometric study showed 1:1 `mole ratio. The rate law derived from the kinetic study under pseudo first order condition is . The rate constant of reaction,  varies inversely with acid concentration, [H+]. The overall rate law is therefore represented as: . The reaction displayed positive salt effect which suggests the activated complex was made up of similar charged species. The reaction was catalysed by addition of formate, HCOO- and potassium, K+ ions and the Michaelis-Menten’s plot gave zero intercept indicating the absence of intermediate complex. A reaction mechanism via an outer-sphere pathway is proposed for this reaction.